Heterospathe fernandoi, a new palm (Areceae, Arecoideae, Arecaceae) from the Philippines - Adorador, Jiro T. (Phytotaxa, 2019)
A new slender clustering palm, Heterospathe fernandoi, from forests on ultramafic soils in Samar, Dinagat, Bucas Grande, and northeastern Mindanao in the Philippines is described and illustrated. It is similar to H. scitula in its general vegetative and reproductive characters but differs in its somewhat persistent leaf sheaths, relatively wider median unicostulate leaflets, and interfoliar inflorescences in which both the axes and perianth are typically coloured light purple to deep maroon during anthesis. Its morphology, habitat, ecology, and conservation status are also discussed.